Best Linear Methods of Approximation of Functions of the Hardy Class H_p - Savchuk, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We determine the exact value of the best linear polynomial approximation of a unit ball of the Hardy space H_p, 1 ≤ p ≤ ∞, on concentric circles Tρ = z ∈ C:|z|=ρ, 0 ≤ ρ < 1, in the uniform metric. We construct the best linear method of approximation and prove the uniqueness of this method.